Physician visits and medication prescriptions for major chronic diseases during the COVID-19 pandemic in Japan: retrospective cohort study. Issue 7 (23rd July 2021) - Osawa, Itsuki; Goto, Tadahiro; Asami, Yuko; Itoh, Noriharu; Kaga, Yasuyuki; Yamamoto, Yuji; Tsugawa, Yusuke
Abstract : Objectives: There have been concerns that patients with chronic conditions may be avoiding in-person physician visits due to fear of COVID-19, leading to lower quality of care. We aimed to investigate changes in physician visits and medication prescriptions for chronic diseases before and during the COVID-19 pandemic at the population level. Design: Retrospective cohort study. Setting: Nationwide claims data in Japan, 2018–2020. Participants: Working-age population (aged 18–74 years) who visited physicians and received any prescriptions for major chronic diseases (hypertension, diabetes and dyslipidaemia) before the pandemic. Outcome measures: The outcomes were the monthly number of physician visits, the monthly proportion of physician visits and the monthly proportion of days covered by prescribed medication (PDC) during the pandemic (April–May 2020, as the first state of emergency over COVID-19 was declared on 7 April, and withdrawn nationally on 25 May). Results: Among 10 346 patients who visited physicians for chronic diseases before the pandemic, we found a temporary decline in physician visits (mean number of visits was 1.9 in March vs 1.7 in April; p<0.001) and an increase in the proportion of patients who did not visit any physicians during the pandemic (15% in March vs 24% in April; p<0.001). Physician visits returned to the baseline in May (the mean number of visits: 1.8, and the proportion of patients who did not visit any physicians: 9%). We observed no clinically meaningful difference in PDC between before and during the pandemic (eg, 87% in March vs 87% in April; p=0.45). A temporary decline in physician visits was more salient in seven prefectures with a larger number of COVID-19 cases than in other areas. Conclusions: Although the number of physician visits declined right after the COVID-19 outbreak, it returned to the baseline one month later; patients were not skipping medications during the pandemic.